Construct validity and reliability of the Bilateral Vestibulopathy Questionnaire (BVQ) - van Stiphout, Lisa; Rolfes, Jeremy; Waardenburg, Sophie; Kimman, Merel; Guinand, Nils; Pérez Fornos, Angélica; Van Rompaey, Vincent; van de Berg, Raymond (Frontiers in Neurology, 2023)
Background The Bilateral Vestibulopathy Questionnaire (BVQ) is a recently developed 54-item Patient Reported Outcome Measure (PROM) that evaluates the clinically important symptoms of bilateral vestibulopathy (BVP) and its impact on daily life. This study aimed to assess the construct validity and reliability of the BVQ in a large BVP cohort. Methods Patients diagnosed with BVP were asked to complete a set of questionnaires, including the BVQ, the EuroQol-5D-5L, the Health Utilities Index, the Dizziness Handicap Inventory, the Hospital Anxiety and Depression Scale, and the Oscillopsia Severity Questionnaire. The construct validity of the BVQ was evaluated by confirmatory and exploratory factor analyses (CFA and EFA), followed by hypotheses testing and known groups validity. Structural properties were explored for each individual item. Reliability was assessed by testing the internal consistency of the BVQ constructs (Cronbach's alpha) and test–retest reliability [intraclass correlation coefficients (ICCs)]. Results A total of 148 patients with BVP (50% women, mean age 66 years) completed the set of questionnaires. The CFA did not show a satisfactory model in the original BVQ. However, the EFA showed a four-factor solution with 20 Likert-scale items related to oscillopsia, imbalance, emotion, and cognition. The succeeding CFA provided evidence for construct validity and an acceptable model of fit. Hypothesis testing confirmed that this shortened version validly measures the constructs to be measured. Statistically significant differences in scores between known groups were found, providing further support for good construct validity. The structural properties were acceptable. Cronbach's alpha confirmed good internal consistency for the four constructs, ranging from 0.80 to 0.89. The ICCs of the 20 Likert-scale items and four visual analog scale (VAS) items were interpreted as good (range 0.76–0.93). Conclusion This study showed evidence of good construct validity of the new shortened version of the BVQ, consisting of four constructs with a total of 20 Likert-scale items and four VAS items. The final 24-item BVQ proved to be a reliable and valid multi-item PROM that captures the clinically important symptoms of BVP and evaluates its impact on daily life. Consequently, the BVQ enables the gathering of high-level evidence of treatment effectiveness in a systematic and quantitative manner.